An investigation to study the combined effect of different infill pattern and infill density on the impact strength of 3D printed polylactic acid parts. (April 2021) - Mishra, Pradeep Kumar; Senthil, P.; Adarsh, S.; Anoop, M.S.
Abstract: The emanation of 3D printing technology has enabled researchers to manufacture complex geometrical structures to design high impact energy-absorbing structure for different laboratory and industrial applications. In the present investigation, an Impact test had been performed to measure the absorbed energy during the plastic deformation of the PLA (Polylactic acid) 3D printed components with the combination of different infill patterns and infill densities. Experimental investigation on specimens through the Izod impact test concluded that at 85% infill density for each infill pattern, the energy absorption is maximum. Results showed that the fracture resistance of specimens was a mutual function of induced stress and crack propagation at the notch area during the impact test and the dynamics of impact failure outlined by mechanics of laminate composite. Highlights: Impact energy absorbing capability of 3D printed specimen depends on infill pattern and infill density. 3D printed PLA specimen with line infill pattern has high impact energy absorbing capability among different infill patterns. Specimens with 85% infill density absorb maximum impact energy compared to other infill density. The fracture rate at the notch area of Izod-impact specimens was majorly driven by crack propagation nature and stress intensity magnitude.